Students Competence And Entrepreneurial (Case Studies In Widyatama University) - Intan Widuri Sakti (Jurnal Ilmiah Akuntansi dan Humanika, 2014)
ABSTRACT Unbalance of the workforce with jobs, making government implement programs to boost entrepreneurship among students. Entrepreneurship is expected to help the nation's economy. Entrepreneurship it is necessary to support the entrepreneurial competence. Competence are ability, skill or individual skill in interacting effectively with the environment and make an impact on others in order to achieve certain goals in a social context that is tailored to the culture, the environment and the situation at hand. This research  was conducted to determine the relationship between entrepreneurial competencies with the students at Widyatama University. Research studies using 40 students as population who are entrepreneur. Data collection was performed using the two-scale entrepreneurship scale (Meredith, 1996; 6) which consists of 30 items and scales of competence (Gullota, 1990; 100) content 36 items. Data analysis to determine the existence of a positive relationship between entrepreneurial competencies with the students was conducted using simple regression analysis. The results showed the number rxy = 0.822 with p = 0.000 (p <0,05). There is a significant positive relationship between the entrepreneurial competence. Effectiveness of regression in this research was 67.5%, showing influence entrepreneurial competencies of 67.5% in research population. Based on this research it can be concluded that there is a significant positive relationship between students competence and entrepreneurship it means higher of students competence  will increase  their entrepreneurial, and conversely, lower of students competence will decrease their entrepreneurial.   Keywords : students competence, entrepreneurial